Identification of a non-canonical G3BP-binding sequence in a Mayaro virus nsP3 hypervariable domain - Neyret, Aymeric; Bernard, Eric; Aïqui-Reboul-Paviet, Olivier; Bakhache, William; Eldin, Patrick; Chaloin, Laurent; Briant, Laurence (Frontiers in Cellular and Infection Microbiology, 2022)
Ras-GTPase activating SH3 domain-binding-proteins 1 (G3BP1) and 2 (G3BP2) are multifunctional RNA-binding proteins involved in stress granules nucleation, previously identified as essential cofactors of Old World alphaviruses. They are recruited to viral replication complexes formed by the Chikungunya virus (CHIKV), Semliki Forest virus (SFV), and Sindbis virus (SINV) via an interaction with a duplicated FGxF motif conserved in the hypervariable domain (HVD) of virus-encoded nsP3. According to mutagenesis studies, this FGxF duplication is strictly required for G3BP binding and optimal viral growth. Contrasting with this scenario, nsP3 encoded by Mayaro virus (MAYV), an arthritogenic virus grouped with Old World alphaviruses, contains a single canonical FGxF sequence. In light of this unusual feature, we questioned MAYV nsP3/G3BPs relationships. We report that G3BP1 and G3BP2 are both required for MAYV growth in human cells and bind nsP3 protein. In infected cells, they are recruited to nsP3-containing cytosolic foci and active replication complexes. Unexpectedly, deletion of the single FGxF sequence in MAYV nsP3 did not abolish these phenotypes. Using mutagenesis and in silico modeling we identify an upstream FGAP amino acid sequence as an additional MAYV nsP3/G3BPs interaction motif required for optimal viral infectivity. These results, therefore, highlight a non-conventional G3BP binding sequence in MAYV nsP3.